Embodied Sensorimotor (Hyper)intensionality - McGregor, Simon (Logic and Logical Philosophy, 2025)
This article aims to stimulate interdisciplinary exchange between logicians and cognitive scientists. In particular, I claim that conceptual analogues of hyperintensionality and intensionality can be found when we apply statistical tools to analyse sensorimotor processes in embodied cognition. When considering the functional correlation between the internal state X of an agent, and the external state Y of its environment, I propose that the precise functional form of the correlation has a hyperintensional flavour, while the abstract information carried by the correlation has a purely intensional flavour. Recent work by Kolchinsky and Wolpert attempts to bring ‘semantics’ to physical correlations by analysing the effects of those correlations on task performance. I argue that this ‘semantic information’ framework currently provides a model for intensional, but not hyperintensional, aspects of belief in a hypothetical mental arithmetic scenario. In general, I suggest that cognitive scientists should be more familiar with the intensional/hyperintensional distinction (for instance, I argue that the ‘Bayesian brain’ approach cannot account for hyperintensional aspects of cognition), and that logicians should be aware of analogues of hyperintension in embodied cognition (for instance, I claim that hyperintensional-like phenomena occur as much in bacteria as in humans).